Compatibility of 5-ethynyl-2′F-ANA UTP with in vitro selection for the generation of base-modified, nuclease resistant aptamers. Issue 35 (28th August 2019) - Levi-Acobas, Fabienne; Katolik, Adam; Röthlisberger, Pascal; Cokelaer, Thomas; Sarac, Ivo; Damha, Masad J.; Leumann, Christian J.; Hollenstein, Marcel
Abstract : A nucleoside triphosphate bearing modifications at both the sugar and the nucleobase level was shown to be compatible with combinatorial methods of in vitro selection. Abstract : A modified nucleoside triphosphate bearing two modifications based on a 2′-deoxy-2′-fluoro-arabinofuranose sugar and a uracil nucleobase equipped with a C5-ethynyl moiety (5-ethynyl-2′F-ANA UTP) was synthesized. This nucleotide analog could enzymatically be incorporated into DNA oligonucleotides by primer extension and reverse transcribed to unmodified DNA. This nucleotide could be used in SELEX for the identification of high binding affinity and nuclease resistant aptamers.